Valoración de la citología para el diagnóstico de tumores en caninos - Rodriguez, Bernardo J.; Ortiz, Laura C.; Garzón, Anderson; Gómez, Luisa F.; Vásquez, Yeimy (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Cytology is a controversial diagnostic tool in veterinary medicine. In Colombia there are no studies about its reliability as a diagnostic tool. The porpoise of this study was to compare accuracy of the cytology with respect to histopathology for the diagnosis of mammary, cutaneous and subcutaneous tumors in dogs. We performed an observational analytic study from July to October 2006. In this study 42 biopsies and 35 fine needle aspiration biopsies (FNAB) of canine mammary, cutaneous and subcutaneous tumors were observed. Samples were obtained from four veterinary clinics in Medellin, Colombia. Samples were processed by rutine methods and they were stained with hematoxilin-eosin and Wright- Giemsa stains. Cytology evaluation was performed by a pathologist and the FNAB by cytology students. The FNAB has a high sensibility to determine malignancy (76.47%), a specificity of 93.33%, positive and negative predictive values of 84.38 and 92.86%, respectively. The concordance between the final diagnosis obtained from FNAB and histopathology was 79%. Cytodiagnosis is a reliable tool to determine the malignancy of mammary cutaneous and subcutaneous tumors in dogs in the pathology laboratory of "Universidad de Antioquia".